Environmental fate of chemicals in societal use - Anton J.M. Schoot Uiterkamp (Journal of Integrative Environmental Sciences)
For a long time, industrial chemicals and chemical products have been increasingly used for practical societal services such as health care, personal care, food preservation, crop protection, housing, and transportation. In most cases, the use of these chemicals has also implied their immediate or delayed release into the environment, often with unforeseen or unintended consequences. This essay poses two questions on this topic: why do large-scale releases of chemicals into the environment still occur and what is the effect of efforts to limit this practice? The essay categorizes chemicals based on their use and their fate in the environment. “Forever chemicals” such as DDT and PFAS form a special category based on their persistence and adverse effects on the health and well-being of humans and other organisms. In recent years, scientific concepts such as exposome and eco-exposome have been developed to systematically characterize, monitor, and measure the adverse effects of chemicals in the environment. At the same time, legislative and regulatory measures have been taken that target all or specific categories of chemicals. Much remains to be done to bring the full life cycle of chemicals in the environment under acceptable control.